A case of Acute Aortic Dissection with Orofacial Pain as the Initial Manifestation. Issue 3 (May 2021) - Naito, Hisaki; Sueta, Daisuke; Ogata, Katsumori; Nagata, Masashi; Hirosue, Akiyuki; Tanaka, Hiromichi; Uezono, Keiji; Okamoto, Ken; Tsujita, Kenichi; Fukui, Toshihiro; Nakayama, Hideki; Kasaoka, Shunji
Abstract: Because the prognosis of acute aortic dissection will be often poor, early diagnosis and assessing severity at the first visit is important. An 83-year-old woman was admitted to an emergency department (ED) with complaints of sudden bilateral upper and lower jaw pain during dinner. Finally, the oral pain moved back pain and she requested an ambulance. Although her vital signs were preserved, she has a left-right difference in blood pressure in her upper limbs. A contrast media-enhanced computed tomography revealed that dissection was found in the ascending aorta in thoracic aorta, which reached the brachiocephalic artery. Therefore, the main symptom in the present case was diagnosed as acute aortic dissection (Stanford type A), an urgent ascending aortic replacement was successfully performed. We experienced an acute aortic dissection whose initial symptom was oral pain. It is a symptom that physicians and dentists need to be aware of that there is a fatal disease where the pain source is different from the patient complaining of pain.